Description of Candida albicans Fungus in The Oral Mucosa of Patients With Fe Deficiency Anemia in RSUD Ciamis - Aditya Nur Romadhon; Mei Widiati; Undang Ruhimat; Euis Tia Istianah (Mukhtabar Journal of Medical Laboratory Technology, 2023)
Background & Objective Indonesia is a developing country where Fe deficiency anemia is common. Fe deficiency anemia is a malnutrition disease caused by a lack of Fe in the patient's body. Fe deficiency anemia is triggered by a lack of Fe in the body for the formation of hemoglobin, causing patients to experience blood deficiency and thinning of oral mucosal epithelial cells which can cause oral candidiasis. Analyzing the description of oral candidiasis in patients with Fe deficiency anemia. Methods  This study is a descriptive study that recruited a total sampling of 17 patients with Fe deficiency anemia. Oral candidiasis in Fe deficiency anemia was measured by planting on sabouraud dextrose agar (SDA) media and sugars media then observed macroscopically and microscopically from SDA and sugars cultures using a microscope. Results Based on the results of the study, 15 (88%) positive respondents and 2 (12%) negative respondents. Conclusion The results of the examination of oral candidiasis as many as 15 samples were affected by oral candidiasis caused by Candida albicans.